Comparing Options for Deriving Chemical Ecotoxicity Hazard Values for the European Union Environmental Footprint, Part II. (14th August 2019) - Saouter, Erwan; Wolff, Deidre; Biganzoli, Fabrizio; Versteeg, Donald
ABSTRACT: Using the European Union's Registration, Evaluation, Authorisation and Restriction of Chemicals (REACH) ecotoxicity data, this paper compares 3 different approaches to calculate final substance toxicity hazard values using the USEtox approach (chronic EC50 + acute EC50/2), using only acute EC50 equivalent data (EC50eq ), and using only chronic no observed effect concentration equivalent (NOECeq) data. About 4008, 4853, and 5560 substance hazard values could be calculated for the USEtox model, acute only, and chronic only approaches, respectively. The USEtox model provides hazard values similar to the ones based on acute EC50 data only. Although there is a large amount of variability in the ratios, the data support acute EC50eq to chronic NOECeq ratios (calculated as geometric mean) of 10.64, 10.90, and 4.21 for fish, crustaceans, and algae respectively. Comparison of the calculated hazard values with the criteria used by the EU chemical Classification, Labelling, and Packaging regulation (CLP) shows the USEtox model underestimates the number of compounds categorized as very toxic to aquatic life and/or having long‐lasting effects. In contrast, use of the chronic NOEC data shows a good agreement with CLP. It is therefore proposed that chronic NOECeq are used to derive substance hazard values to be used in the EU Environmental Footprint. Due to poor data availability for some chemicals, the uncertainty of the final hazard values is expected to be high. Integr Environ Assess Manag 2019;15:796–807. © 2019 The Authors. Integrated Environmental Assessment and Management published by Wiley Periodicals, Inc. on behalf of Society of Environmental Toxicology & Chemistry (SETAC). Key Points: The European Union (EU) Registration, Evaluation, Authorisation and Restriction of Chemicals (REACH) database has been used to calculate aquatic toxicity hazard values for 5560 chemicals substances to be used in the EU Environmental Footprint. Three methods to calculate hazard values have been compared using all available acute and chronic reference points. Hazard values derived from chronic no observed effect concentration equivalent (NOECeq ) showed the best agreement with the chemical toxicity ranking as defined within the EU chemical Classification, Labelling, and Packaging regulation (CLP) regulation. Acute EC50eq to chronic NOECeq ratios of 10.64, 10.90, and 4.21 for fish, crustaceans, and algae, respectively, have been calculated.